Strategi Pengembangan Kompetensi SDM Pertahanan untuk Adaptasi di Era VUCA - Surdi Muhamad Lailan Muha; Simon Ponimen Silitonga (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
The VUCA era (Volatility, Uncertainty, Complexity, Ambiguity) presents significant challenges for the defense sector, requiring the development of human resources (HR) competencies that are capable of adapting to dynamic changes. Defense HR plays a vital role in ensuring national security through technical skills, leadership, and high flexibility. This study aims to identify strategies for developing relevant and adaptive defense HR competencies in response to the VUCA era, focusing on continuous education development, technology-based training, and the formation of responsive character. The results of the study indicate that the development of defense HR competencies should include the enhancement of soft skills such as leadership, communication, and critical thinking, as well as the adoption of advanced technologies such as Artificial Intelligence (AI) and Virtual Reality (VR) simulations. Furthermore, international cooperation is an important element in knowledge and technology transfer. In conclusion, an effective defense HR development strategy must integrate technology-based training, strengthening soft skills, and accelerating decision-making processes. It is recommended that policies focus on providing adequate budgets, improving bureaucratic efficiency, and establishing strategic cooperation with educational institutions and international partners. This approach is expected to create resilient, innovative defense HR that is ready to face the challenges of the VUCA era.